Система поддержки принятия решений по выбору структуры системы мониторинга - Skatkov, A. V.; Voronin, D. Yu.; Danilchuk, D. N. (PE "Politekhperiodika", Book and Journal Publishers, 2008)
The problem of structural synthesis of monitoring systems is considered. A decision support system for selecting the structure of a monitoring system and the polling discipline of nodes within a fragment of a computer network is described. At the first stage of synthesis, the classification notation of monitoring systems proposed by the authors is applied. At subsequent stages, simulation and analytical modeling tools are used, along with adaptive algorithms. The results of studies carried out with the aid of the proposed software tool are presented.